Eating habits of women of childbearing age from Varna, Bulgaria. (30th September 2020) - Chamova, R; Dimitrova, T
Abstract: Background: Eating habits of childbearing age women are an important public health determinant. The inappropriate dietary pattern of women in reproductive age leads to deviations in their nutritional status with possible adverse health consequences for them and their offspring. Both malnutrition and over nutrition can adversely affect reproductive abilities of women as well as the course and outcome of a possible pregnancy. Methods: We conducted a cross-sectional study on dietary habits of 107 women, aged 19 to 42 years, in Varna, Bulgaria between March-December 2019. Exclusion criteria were pregnancy and lactation. A questionnaire was applied composed of questions on diet, dietary pattern, food frequency consumption, and the respondents' physical activity. The results were compared with the National Food Based Dietary Recommendations for Adults in Bulgaria. Data was statistically analysed with SPSS version 19. Results: The average age of participants was 25.65 ± 7.48 years. 22.4% of the surveyed women followed no particular diet. 35.5% and 30.8% of the respondents had daily consumption of milk and dairy products respectively. Meat consumption 3-4 times a week was reported by 29.9% of the respondents. Only 1/4 of the respondents consumed fish each week. The relative share of women who did not consume fish was 10.3%. Daily consumption of fruits and vegetables was 42.1% and 57% respectively. Conclusions: The majority of the surveyed women does not follow the National recommendations for consumption frequency of milk, dairy products, meat, fish, fruits and vegetables. Respondents who do not consume fish, meat or milk and dairy products are at risk of deficiencies of both micronutrients and macronutrients. It's necessary to raise awareness about healthy eating and associated health risks. Key messages: Nutrition of women of childbearing age is an important factor affecting public health. Inadequate dietary habits before conception raises the risk for the course and outcome of pregnancy with consequences for offspring health.